Dental erosion` prevalence and its relation to isotonic drinks in athletes: A systematic review and meta-analysis - de Queiroz Gonçalves, P. H. P.; Guimarães, L. S.; de Azeredo, F. N. A.; Wambier, L. M.; Antunes, L. A. A.; Antunes, L. S. (Sport Sciences for Health, 2020)
Purpose To estimate the global prevalence of dental erosion and to evaluate whether there is scientific evidence that the use of isotonic drinks could increase the risk of this condition in athletes.